Queer phenomenology: Orientations, objects, others - Ahmed, Sara (Duke University Press, 2006)
"In this groundbreaking work, Sara Ahmed demonstrates how queer studies can put phenomenology to productive use. Focusing on the “orientation” aspect of “sexual orientation” and the “orient” in “orientalism,” Ahmed examines what it means for bodies to be situated in space and time. Bodies take shape as they move through the world directing themselves toward or away from objects and others. Being “orientated” means feeling at home, knowing where one stands, or having certain objects within reach. Orientations affect what is proximate to the body or what can be reached. A queer phenomenology, Ahmed contends, reveals how social relations are arranged spatially, how queerness disrupts and reorders these relations by not following the accepted paths, and how a politics of disorientation puts other objects within reach, those that might, at first glance, seem awry. Ahmed proposes that a queer phenomenology might investigate not only how the concept of orientation is informed by phenomenology but also the orientation of phenomenology itself. Thus she reflects on the significance of the objects that appear—and those that do not—as signs of orientation in classic phenomenological texts such as Husserl’s Ideas. In developing a queer model of orientations, she combines readings of phenomenological texts—by Husserl, Heidegger, Merleau-Ponty, and Fanon—with insights drawn from queer studies, feminist theory, critical race theory, Marxism, and psychoanalysis. Queer Phenomenology points queer theory in bold new directions." – Tiré du site de l'éditeur
Keywords: 2000 à aujourd'hui; 2000-2009; LGBTQIA2+; approches et analyses; corps; cours; discipline; fem1000; féminisme décolonial; identité sexuelle; identités LGBTQIA2+; incontournable; lit4700; militance; occident; orient; philosophie; phénoménologie; premier cycle; périodes historiques; queer; queer of color; rapports de domination; rapports sociaux de sexe; sciences humaines; sex3383; thématiques; violences; études culturelles

Queer zones: politique des identités sexuelles et des savoirs - Bourcier, Marie-Hélène (Amsterdam, 2006)
Publié pour la première fois en 2001, ce livre pionnier a permis l'ouverture d'un espace théorique et politique queer en France. Il s'agit d'une boîte à outils destinée aux activistes en quête de cultures et de politiques sexuelles qui ne soient pas (homo ou hétéro) normatives. Stimulants et provocants, les textes réunis dans ce recueil constituent également une introduction critique à la déconstruction des genres et aux travaux de Judith Butler et de Michel Foucault. Ils mettent de plus en évidence l'apport des subcultures trans, butch et SM à une réflexion plus large sur les relations entre pouvoir et savoir, ainsi que le formidable potentiel des sexualités dissidentes et la continuité politique entre féminisme pro-sexe et activisme queer. Cette nouvelle édition comprend trois essais inédits sur le " devenir femme " de Deleuze, l'utopie sexuelle urbaine de Gayle Rubin et la post-pornographie selon Annie Sprinkle.
Keywords: approches et analyses; cours; discipline; fem1000; har4600; histoire; identités LGBTQIA2+; lit3220; militance; personnes trans*; politique; premier cycle; queer; sciences humaines; sexualité; thématiques; violences

Queering the Binaries: Transsituated Identities, Bodies, and Sexualities - Cromwell, Jason (The transgender studies reader, 2006)
Keywords: 1900-1999; approches et analyses; corps; cours; discipline; fem1000; histoire; identités LGBTQIA2+; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques; états-unis

Anti-Essentialism and Intersectionality - Grillo, Tina (Theorizing feminisms a reader, 2006)
'What is oppression ?' 'What should be done about it ?' Organized around these questions, Theorizing feminisms : a reader provides an overview of theoritical feminist writing about the quest for gender justice. Incorporating both classic and cutting-edge material, the reader takes into account the full diversity of women, highlighting the effects of race, ethnicity, nationality, class, sexuality, and religion on women's experience. Theorizing feminisms is organized into four sections and includes fifty-four essays. The first section introduces several basic concepts commonly employed when thinking about sexism - oppression, social construction, essentialism, intersectionality, gender, race, and class - and also raises questions about the perspective and legitimacy of the theorist. The second section surveys three approaches that attempt to characterize in a general way the source of injustice toward women : humanist feminism ('the sameness approach'), gynocentric feminism ('the difference approach'), and dominance feminism. Offering an alternate perspective, the third section introduces two 'localizing' approaches, grounded in postmodernism and identity politics, respectively. Skeptical of theories that attempt to analyze social phenomena across history and culture, authors in this section challenge, rather than answer, the text's organizing questions. The final section explores the relationship of feminism theory to three liberatory projects - postcolonialism, neo-materialism, and queer theory - that do not characterize themselves as feminist, yet take gender as a significant category of analysis. Each section opens with an introduction and each essay is followed by helpful study questions. the majority of the essays are presented in their entirety. Theorizing feminisms underscores the strong connection between feminist theory and practice by including essays that illustrate important political inspirations or applications of each theoritical approach. It also presents versions of the same approach from various points in history, revealing feminist theory to be dynamic and evolving, rather than static. Ideal for interdisciplinary courses in feminist theory, this volume will also serve as an invaluable reference for current and future generations of theorists."
Section: 1 vol. (XIX-564 p.) ; 24 x 19 cm
Keywords: 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; cours; discipline; essentialisme; intersectionnalité; justice sociale; phi4336; philosophie; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; thématiques; théorie féministe

La loi du genre : une histoire culturelle du troisième sexe - Murat, Laure (Fayard, 2006)
Homme ou femme. Existe-t-il un espace viable entre ou hors ces deux catégories ? Une invention théorique et poétique a tenté de fournir, au cours de l'histoire, une réponse à cette question : le " troisième sexe ", celui qui défierait la loi du genre. L'expression désigne, à partir du XIXe siècle, les figures considérées comme déplacées par rapport aux canons de la virilité et de la féminité : les " tantinettes " traquées par la police dans le Paris de Balzac, les saphistes de roman et les invertis étudiés par la psychiatrie, les " fastueux travestis " des bals populaires, les femmes émancipées de la Belle Epoque et les premiers transsexuels opérés des années 1930. Derrière toutes ces figures dissidentes, l'idée d'un " troisième sexe " provoque, dérange et renvoie la société à cette énigme inépuisable : que signifie vraiment être une " femme " ou un " homme " ? Exploitant des archives inédites de la police, des textes méconnus de la sexologie ou de la littérature, Laure Murat a élaboré ici une analyse inattendue et passionnante, éclairant d'un jour nouveau l'archéologie des discours sur les questions de genre que notre époque ne cesse d'interroger.
Keywords: 1800-1899; 1900-1999; LGBTQIA2+; analyse de discours; approches et analyses; belle époque; cours; discipline; discours dominant; europe; fem1000; france; genre; his4860; histoire; homophobie; identités LGBTQIA2+; paris; premier cycle; périodes historiques; queer; rapports sociaux de sexe; régions géographiques; sciences humaines; sexualité; sexualités dissidentes; systèmes d'oppressions; thématiques; transphobie; troisième sexe

The transgender studies reader - Stryker, Susan; Whittle, Stephen (Routledge, 2006)
Although the term "transgender" itself has achieved familiarity only within the past decade, this authoritative collection of articles demonstrates that the study of behaviors, bodies, and subjective identities which contest common Eurocentric notions of gender has a history stretching back at least to the early 20th century. Transgender studies is the latest area of academic inquiry to grow out of the exciting nexus of queer theory, feminist studies, and the history of sexuality. Because transpeople challenge our most fundamental assumptions about the relationship between bodies, desire, and identity, the field is both fascinating and contentious. The Transgender Studies Reader puts between two covers fifty influential texts with new introductions by the editors that, taken together, document the evolution of transgender studies in the English-speaking world. By bringing together the voices and experience of transgender individuals, doctors, psychologists, and academically-based theorists, this volume will be a foundational text for the transgender community, transgender studies, and related queer theory.
Keywords: 1900-1999; amériques; anthologie; approches et analyses; cours; discipline; fem1000; histoire; identités LGBTQIA2+; interdisciplinarité; occident; personnes trans*; premier cycle; périodes historiques; queer; régions géographiques; sciences humaines; sexualité; thématiques